Review—Nanocarbon-Based Multi-Functional Biointerfaces: Design and Applications. (1st January 2016) - Arugula, Mary; Simonian, Alex
Abstract : Nanocarbons are promising materials in a growing list of applications due to their unique intrinsic and potentially tunable properties. Carbon nanotubes are one of the most favorable nanocarbons used in biosensors R&D due to their excellent structural and electronic properties. Scaffolding of different functionally active biopolymers on CNTs and their further layer-by-layer (LbL) assembly on the appropriate interfaces allow creation of new insights and concepts for the development of multiple novel technological biointerfaces based on intercalation of CNTs covered with different oppositely charged biopolymers and enzymes. We concentrate on how different enzymes assembled at the same interface by the LbL technique can operate in different modes in the construction of novel bioelectronic applications. In this review we focus on the design of unique multifunctional devices for biomedical, environment and energy applications. This paper reviews the research results of the last several years and summarizes the carbon nanotubes application in biosensors.